Bacteroides fragilis strain ZY-312 promotes intestinal barrier integrity via upregulating the STAT3 pathway in a radiation-induced intestinal injury mouse model - Zhou, Qian; Shen, Binhai; Huang, Ruo; Liu, Hongbin; Zhang, Wendi; Song, Mengyao; Liu, Ke; Lin, Xinlong; Chen, Shuze; Liu, Yangyang; Wang, Ye; Zhi, Fachao (Frontiers in Nutrition, 2022)
Radiation-induced intestinal injury is characterized by intestinal barrier impairment. However, the therapeutic effects of probiotics for intestinal epithelial barrier repair in a mouse model of radiation-induced intestinal injury remain unclear. Previously, we isolated a strain of Bacteroides fragilis from the feces of a healthy infant and named it as B. fragilis strain ZY-312 (B. fragilis). In this study, we showed that B. fragilis can ameliorate radiation-induced intestinal injury in mice, manifested by decreased weight loss, intestinal length shortening, and intestinal epithelial cell (IEC) shedding. Moreover, we found that B. fragilis promoted IEC proliferation, stem cell regeneration, mucus secretion, and tight junction integrity by upregulating the STAT3 signaling pathway, through an experimental verification in Stat3△IEC mice (STAT3 defects in intestinal epithelial cells). Thus, the underlying protective mechanism of B. fragilis in radiation-induced intestinal injury is related to IEC proliferation, stem cell regeneration, goblet cell secretion, and tight junction repair via activation of the STAT3 signaling pathway. In addition, the therapeutic effects of B. fragilis were studied to provide new insights into its application as a functional and clinical drug for radiation-induced intestinal injury after radiotherapy.